Comparative Study of Mirabegron and Tolterodine for the Treatment of Overactive Bladder in Women - Fahad Mehmood Khokhar, Shah Jahan-Ur-Rehman, Muhammad Usman Anwar, Hafiza Sabiha Akhtar, Muhammad Abdullah Haris, Mahnoor Naveed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Overactive bladder is a disease of multifactorial etiology resulting from various potential pathophysiological mechanisms. Tolterodine and Mirabegron are established treatment therapy for patients with overactive bladder owing to its efficacy and safety. Tolterodine, muscarinic receptor antagonist, acts on both M2 and M3 receptors and Mirabgron is a β3-adrenoceptor agonist. Objective: To compare the efficacy and safety of Mirabegron versus Tolterodine for the treatment of overactive bladder in women. Study Design: Randomized clinical trial study Place and Duration of Study: Department of Urology, Jinnah Hospital Lahore from 10th April 2022 to 9th April 2023. Methodology: One hundred and sixty female patients were enrolled. They were divided in two groups; each group comprised equal number of patients. Group A patients were given Mirabegron 50mg once daily for 12 weeks and group B were given Tolterodine 2mg twice daily for 12 weeks. The overactive bladder symptom score (OABSS) was calculated by using prescribed questionnaire for each patient before start of therapy and at each follow up visits at 2nd, 4th, 8th and 12th week of treatment. Side effects like dry mouth, constipation, headache, dizziness and blurred vision were also noted. Results: The mean ages were 38.67±13.30 years in Mirabegron group, while in Tolterodine group, 38.45±11.43 years. The mean body mass index was 26.33±6.79 kg/m2 in Mirabegron group and in Tolterodine group, body mass index was 30.13±6.62 kg/m2. The pre-treatment mean over active bladder symptoms score was 13.70±1.06 in Mirabegron group while in Tolterodine group, OABSS was 13.60±1.14. After the treatment, mean OABSS was 5.41±1.13 in Mirabegron group and in Tolterodine group, OABSS was 6.98±0.92. Regarding after treatment, 22 (27.5%) patients had constipation in Mirabegron group and 37 (46.2%) patients had constipation in Tolterodine group. After treatment, in Mirabegron group, 24 (30%) patients were presented with dry mouth and in Tolterodine group, 38(47.5%) patients had dry mouth. Regarding after treatment, 21(26.2%) patients were presented with complaint of dizzines in Mirabegron group and 37(46.2%) patients in Tolterodine group. After treatment, 19(23.8%) patients had headache in Mirabegron group and 33(41.2%) patients had headache in Tolterodine group. According to after treatment, in Mirabegron group, there were 21(26.2%) patients with complaint of blurred vision and 37 (46.2%) patients presented with blurred vision. The efficacy in Mirabegron group was 93.8% and in Tolterodine group, 46.2%. Conclusion: Mirabegron is more effective than tolterodine for the treatment of overactive bladder among women in terms of reducing over active bladder symptoms score after treatment. Keywords: Mirabegron, Tolterodine, Overactive bladder